Comparative Study of the Priming Effect of Abscisic Acid on Tolerance to Saline and Alkaline Stresses in Rice Seedlings - Zhonghui Feng; Guanru Lu; Miao Sun; Yangyang Jin; Yang Xu; Xiaolong Liu; Mingming Wang; Miao Liu; Haoyu Yang; Yi Guan; Tianhe Yu; Jiafeng Hu; et al. (Agronomy, 2023)
The plant hormone abscisic acid (ABA) regulates the plant response to environmental stress; therefore, ABA priming is an effective strategy for enhancing stress tolerance in rice. In this study, we investigated the priming effects of 1 and 5 µM ABA on the biochemical and physiological traits associated with seedling growth performance in two rice cultivars exposed to saline (100 mM NaCl) and alkaline (15 mM Na2CO3) stress via root drenching. ABA pretreatment effectively reduced damage in rice seedlings by mitigating the increases in Na+/K+ ratio, membrane injury, contents of Na+, malondialdehyde, hydrogen peroxide, and superoxide anion radical, and prevented reductions in K+ and total chlorophyll contents, and ROS-related enzyme activities in both cultivars under saline and alkaline stresses. Rice seedlings with ABA pretreatment under alkaline stress had a stronger ability to maintain ion homeostasis, eliminate ROS, and induce changes in endogenous ABA levels via the upregulation of OsHKT1;5, OsSOS1, OsNHX5, OsPOX1, OsCATA, OsNCED3, OsSalT, and OsWsi18 and downregulation of OsRbohA than under saline stress. The saline–alkaline (SA)-sensitive cultivar demonstrated greater sensitivity to the priming effect of ABA than that of the SA-tolerant cultivar under both stress conditions. These findings have implications for rice adaptation to SA soils.